Efficacy of Chinese herbal medicine Zengru Gao to promote breastfeeding: a multicenter randomized controlled trial - Shuaishuai Wang; Chi Zhang; Cuishan Li; Daocheng Li; Ping He; Zhaojuan Su; Yanling Li; Yiling Ding; Aiping Lu (BMC, 2018)
Abstract Background Breastfeeding is recommended worldwide but not fully practiced. The first week after childbirth is regarded as a critical period for increasing breast milk production. The aim of the study was to investigate whether Chinese herbal medicine Zengru Gao would result in more women breastfeeding in the first week after childbirth. Methods A multicenter randomized controlled trial was conducted of 588 mothers considering breastfeeding in China. Among the mothers of the intervention group, the intervention included Chinese herbal medicine Zengru Gao; among those of the control group, it did not. Primary outcomes were the percentages of fully and partially breastfeeding mothers. Secondary outcome was baby's daily formula intake. Results At 3 d and 7 d after delivery, significant differences were found in favour of Zengru Gao group on the percentage of full/ partial breastfeeding (Z = − 3.0037, p = 0.0027). At day 7, the percentage of full/ partial breastfeeding of the active group increased to 71.48%/20.70% versus 58.67%/30.26% in the control group, the differences remained significant (Z = − 3.0037, p = 0.0027). No statistically significant differences were detected on primary measures at 1 d. While intake of formula differed between groups at 1 d and 3 d, this difference did not achieve statistical significance, but this difference was apparent by 7 d (55.45 ± 115.39 ml/day vs 90.66 ± 153.89 ml/day). Conclusion In conclusion, Chinese Herbal medicine Zengru Gao enhanced breastfeeding success during one week postpartum. The approach is acceptable to participants and merits further evaluation. Trial registration ChiCTR-IPR-15007376, December 11, 2015.